Apigenin Attenuates Inflammation in Experimentally Induced Acute Pancreatitis-Associated Lung Injury. (3rd May 2016) - Basios, Neofitos; Lampropoulos, Pavlos; Papalois, Apostolos; Lambropoulou, Maria; Pitiakoudis, Michael K.; Kotini, Athanasia; Simopoulos, Constantinos; Tsaroucha, Alexandra K.
ABSTRACT: Background: Acute pancreatitis is associated with acute lung injury. The aim of the present study is to evaluate alterations of lungs in an experimental model of acute pancreatitis (AP) following both bilio-pancreatic duct obstruction close to the duodenum. Acute pancreatitis is a common disease with significant mortality. This situation makes the need of finding protective factors for the lung parenchyma, imperative. In the present study there is an effort to clarify the role of apigenin, a substance which is well known for its antioxidant and anti-inflammatory effects, on lung injury, following acute pancreatitis in rats. Materials and methods: In the present study, 126 male Wistar-type rats 3–4 months old and 220–350 g weight were used. At time 0 we randomly assigned the following groups: Group Sham: Rats were subjected to virtual surgery. Group Control: Rats were subjected to surgery for induction of acute pancreatitis. Group Apigenin: Rats were subjected to surgery for induction of acute pancreatitis and enteral feeding with apigenin. Immunochemistry for TNF-α and IL-6 as well as MPO activity were measured at predetermined time intervals 6, 12, 24, 48, and 72 h, in order to evaluate architectural disturbances of the lung tissue. Results: From the pathological reports we realized that comparing the control group with the apigenin group, there is an improvement of lung tissue damage following apigenin administration, with statistical significance. Apigenin reduces most histopathological alterations of the pulmonary tissue, reduces MPO and TNF-α activity at 48 hours and, furthermore, reduces IL-6 activity at 72 hours post-administration. Conclusions: Oral Apigenin administration in rats, following experimental induced acute pancreatitis, seems to be protective on the lung tissue. Apigenin administration to humans could potentially ameliorate acute lung injuries. However, special caution is required for humans' use, as more detailed studies are needed.